Analisis Penerapan Konsep Jaminan Fidusia dalam Pembiayaan Perbankan Syaraiah di Indonesia - Defitri Arifah Zulfikar (Lembaga Pengembangan Kinerja Dosen, 2025)
Financing in Indonesia, especially banks, is very important, especially for business actors, this is a natural thing considering that banks have a strategic role in national development in order to realize a just and prosperous Indonesian society. Regulations regarding Sharia financing are regulated in Law No. 10 of 1945 and Article 1 number 2 of Law No. 10 of 1998 concerning amendments to Law No. 7 of 1992 concerning Sharia Banking (hereinafter referred to as the banking law) defines a bank as a business entity that collects funds from the community in the form of deposits and distributes them back to the community in the form of credit and/or in the form of claims in order to improve the standard of living of the people, but there is an inconsistency in the regulation in terms of guarantees. This legal provision continues until the implementation of the Sharia Banking Law, because there are no legal regulations governing sharia guarantees, therefore in terms of sharia banking practices, the guarantee procedures used by conventional banking are still applied, namely fiduciary guarantees and mortgage rights.